Photocatalytic degradation of carbofuran by TiO2-coated activated carbon: Model for kinetic, electrical energy per order and economic analysis. (1st October 2016) - Vishnuganth, M.A.; Remya, Neelancherry; Kumar, Mathava; Selvaraju, N.
Abstract: The photocatalytic removal of carbofuran (CBF) from aqueous solution in the presence of granular activated carbon supported TiO2 (GAC-TiO2 ) catalyst was investigated under batch-mode experiments. The presence of GAC enhanced the photocatalytic efficiency of the TiO2 catalyst. Experiments were conducted at different concentrations of CBF to clarify the dependence of apparent rate constant (kapp ) in the pseudo first-order kinetics on CBF photodegradation. The general relationship between the adsorption equilibrium constant (K) and reaction rate constant (kr ) were explained by using the modified Langmuir-Hinshelwood (L-H) model. From the observed kinetics, it was observed that the surface reaction was the rate limiting step in the GAC-TiO2 catalyzed photodegradation of CBF. The values of K and kr for this pseudo first-order reaction were found to be 0.1942 L  mg −1 and 1.51 mg L −1  min −1, respectively. In addition, the dependence of kapp on the half-life time was determined by calculating the electrical energy per order experimentally ( E EO experimental) and also by modeling ( E EO model). The batch-mode experimental outcomes revealed the possibility of 100% CBF removal (under optimized conditions and at an initial concentration of 50 mg L −1 and 100 mg L −1 ) at a contact time of 90 min and 120 min, respectively. Both L-H kinetic model and E EO model fitted well with the batch-mode experimental data and also elucidated successfully the phenomena of photocatalytic degradation in the presence of GAC-TiO2 catalyst. Highlights: GAC-TiO2 photocatalyst has increased the CBF removal in the reactor. 1/kapp and initial CBF concentration has proportional linear relationship. CBF removal was analyzed by electrical energy per order (EEO ) concept. E EO was found to increase with an increase in initial CBF concentration. Operating cost declined with an increase in initial CBF concentration.